Pendampingan Kegiatan Pemberian Makanan Tambahan Anak Usia Dini di TK Negeri Pembina Kabawetan - Indrawati, Indrawati; Agustriana, Nesna; Sari, Dwi Lyna; Nasution, Siyyella Tika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service aims to improve the knowledge and skills of teachers and parents in preparing and providing healthy, nutritious, and attractive supplementary food for early childhood at TK Negeri Pembina Kabawetan. The problem faced by partners is the rarity of providing supplementary food in accordance with the Technical Guidelines for Providing Supplementary Food Based on Local Food from the Ministry of Health. The implementation method uses a demonstration approach and direct practice of making supplementary food menus using local food ingredients. The activity was carried out for 8 months involving 3 lecturers and 3 students as assistants. The results showed an increase in teachers' knowledge about balanced nutrition and techniques for preparing supplementary food menus, as well as improved skills in making attractive food menus using local ingredients. The outputs include a supplementary food menu guide, journal publications, and video documentation. This program is expected to be sustainable with teachers ability to independently prepare supplementary food menus to support stunting prevention in early childhood.